A Modified Accelerated Overrelaxation (MAOR) scheme for solving the shifted Grünwald estimation fractional Poisson equation - Nik Amir Syafiq; Mohamed Othman; Senu, Norazak; Ismail, Fudziah (Academic Publications, 2022)
This research studies the Modified Accelerated Overrelaxation (MAOR) scheme on fractional Poisson equation. The equation is discretized using the fractional finite difference method with the shifted GrГјnwald estimate. The superiority of this scheme is shown through comparison with previous well known relaxation schemes. This research also presents the convergence analysis for this scheme. Then the numerical result is used to compare and discuss all the schemes.